2000
DOI: 10.1080/10408410091154200
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics ofAzospirillum brasilensein Relation to Cell Aggregation and Attachment to Plant Roots

Abstract: The free-living bacteria of the genus Azospirillum live in close association with plant roots and represent one of the best-characterized plant growth promoting rhizobacteria (PGPR). The attachment of Azospirillum to the roots is essential for the establishment of an efficient association with the host plant. Azospirillum cells are able to aggregate under certain environmental conditions, leading to the formation of bacterial flocs. The bacterial surface plays an important role in the establishment of the bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(82 citation statements)
references
References 61 publications
5
72
0
5
Order By: Relevance
“…Azospirilla are known for their capacity to aggregate and flocculate under diverse stress conditions. Previous studies have suggested the involvement of extracellular polysaccharides in cell aggregation (5). The concentrations of EPS produced by four different strains of A. brasilense differing in their ability to aggregate increased with the extent of aggregation (3).…”
Section: Discussionmentioning
confidence: 98%
“…Azospirilla are known for their capacity to aggregate and flocculate under diverse stress conditions. Previous studies have suggested the involvement of extracellular polysaccharides in cell aggregation (5). The concentrations of EPS produced by four different strains of A. brasilense differing in their ability to aggregate increased with the extent of aggregation (3).…”
Section: Discussionmentioning
confidence: 98%
“…Differences in the exopolysaccharide and capsular polysaccharide contents between wild-type and mutant strains can also explain the ability to aggregate displayed by the latter strain in this study. Azospirilla are known for their capacity to aggregate and flocculate under diverse stress conditions, and previous studies have shown that extracellular polysaccharides are involved in cell aggregation (1,3,21,32). Although the mutant strain's ability to adhere to roots is greater than that of the wild type, no difference in root colonization was observed between the two strains.…”
Section: Discussionmentioning
confidence: 99%
“…This method was shown to be more sensitive and more specific than the Salkowski-based colorimetric technique (10). For the reaction, 1 ml of reagent R1, consisting of 12 g of FeCl 3 per liter in 7.9 M H 2 SO 4 , was added to 1 ml of a sample supernatant, mixed well, and left in the dark for 30 min at room temperature. Absorbance was measured at 530 nm.…”
mentioning
confidence: 99%
“…EPS and CPS play a major role in the interaction of A. brasilense with plant roots (Jofré et al, 2004;Burdman et al, 2000b). It has been proposed that A. brasilense cells adhere to plant roots in two steps: while the first step, likely mediated by polar flagella, is relatively rapid and reversible, in the second step, named the anchoring phase, the cells are anchored firmly and irreversibly to the plant roots, in a process mediated by EPS and CPS (Michiels et al, 1991;Moens & Vanderleyden, 1996;Steenhoudt & Vanderleyden, 2000).…”
Section: Introductionmentioning
confidence: 99%